Interactions of energetic electrons with ULF waves triggered by interplanetary shock: Van Allen Probes observations in the magnetotail. Issue 10 (21st October 2014) - Hao, Y. X.; Zong, Q.‐G.; Wang, Y. F.; Zhou, X.‐Z.; Zhang, Hui; Fu, S. Y.; Pu, Z. Y.; Spence, H. E.; Blake, J. B.; Bonnell, J.; Wygant, J. R.; Kletzing, C. A.
Abstract We present in situ observations of a shock‐induced substorm‐like event on 13 April 2013 observed by the newly launched Van Allen twin probes. Substorm‐like electron injections with energy of 30–500 keV were observed in the region from L∼5.2 to 5.5 immediately after the shock arrival (followed by energetic electron drift echoes). Meanwhile, the electron flux was clearly and strongly varying on the ULF wave time scale. It is found that both toroidal and poloidal mode ULF waves with a period of 150 s emerged following the magnetotail magnetic field reconfiguration after the interplanetary (IP) shock passage. The poloidal mode is more intense than the toroidal mode. The 90° phase shift between the poloidal mode Br and Ea suggests the standing poloidal waves in the Northern Hemisphere. Furthermore, the energetic electron flux modulations indicate that the azimuthal wave number is ∼14. Direct evidence of drift resonance between the injected electrons and the excited poloidal ULF wave has been obtained. The resonant energy is estimated to be between 150 keV and 230 keV. Two possible scenaria on ULF wave triggering are discussed: vortex‐like flow structure‐driven field line resonance and ULF wave growth through drift resonance. It is found that the IP shock may trigger intense ULF wave and energetic electron behavior at L∼3 to 6 on the nightside, while the time profile of the wave is different from dayside cases.